Insights into the potential of water conservation in irrigated agriculture: a case study from the arid Mediterranean highlands - Amdar, Nafn; Anwar, A.; Elmahdi, A.; Al‑Bakri, J.; Jewitt, G.; Mul, M. (Springer, 2025)
Jordan’s Amman-Zarqa (AZ) basin faces increasing water scarcity due to increasing demands and persistent groundwater over-abstractions for irrigation. To address this issue, water conservation has been set as a national strategy, and several initiatives aiming to conserve water in irrigated agriculture have been implemented in the basin’s highlands. This study evaluates the impact of water conservation technologies (WCTs) on irrigation water savings in the AZ basin highlands. Monthly data on irrigation application were collected from 22 farms over three crop seasons (2019–2022) for four dominant orchards. Farm-scale water savings were calculated and projected to the basin scale under two scenarios: a sustainability scenario aligning groundwater abstraction with irrigation needs under WCTs and an economic scenario expanding irrigated areas using the saved water. Results show that irrigation efficiency before the influence of WCTs was below 55%, with farmers applying an average of 1277 mm/year. After implementing WCTs and farmers fine-tuning their irrigation practices, irrigation application decreased to an average of 795 mm/year, resulting in 38% water savings. Projecting these savings basin-wide, WCTs could conserve 44 Mm3/year of water under the sustainability scenario. The results provide a solid basis for informing water conservation targets in this region. However, successful water conservation using WCTs depends on farmer-led testing to ensure reduced irrigation does not compromise crop yields. Pilot programs supported by trusted technical advice through farmer field schools and appropriate incentives can achieve sustainable water conservation in this region. Concurrently, monitoring is required to regulate irrigation expansion as it could undermine water savings.